Evaluation of finger photoplethysmography fitness index on young women with cardiovascular disease risk factors - Musilawati Muhajir,; Amilia Aminuddin,; Azizah Ugusman,; Norizam Salamt,; Zanariyah Asmawi,; Aini Farzana Zulkefli,; Muhammad Firdaus Azmi,; Kalaivani Chellappan,; Nor Anita Megat Mohd Nordin, (Penebit Universiti Kebangsaan Malaysia, 2018)
The use of photoplethysmography (PPG) as one of cardiovascular disease (CVD) marker has got more attention due to its simplicity, noninvasive and portable characteristics. Two new markers had been developed from PPG namely PPG fitness index (PPGF) and vascular risk prediction index (VPRI). The aim of the present study was to compare PPGF level between young women with and without CVD risk factors, to investigate the relationship between PPGF with other CVD markers and to assess the sensitivity of VRPI in classifying young women that have CVD risk factors. A total of 148 young women aged 20-40 years old with and without CVD risk factors were involved in this study. CVD risk factors comprised of abdominal obesity, hypertension, dyslipidemia, smoking and family history of premature CVD. Subjects were categorized into healthy or having CVD risk factor. Measurements taken were anthropometric data, blood pressure, lipid profile, pulse wave velocity (PWV), augmentation index (AIx), high sensitivity C-Reactive Protein (hs-CRP), PPGF and VRPI. SPSS version 20 was used for data analysis with p<0.05 as significant value. The mean subjects’ age was 29.97±5.27 years old. There was no difference in PPGF level between groups (p>0.05). PPGF was independently determined by PWV (β=-0.31, p<0.001) and height (β=0.16, p=0.04). VRPI had 77.9% sensitivity in identifying subjects with CVD risk factor. In conclusion, PPGF correlates with PWV and has potential to be an indicator of aortic stiffness while VRPI is sensitive to classify those with CVD risk factor.